The Influence Of Fartlek Training On Maximum Aerobic Capacity Of Futsal Extracurricular Students At SMPN 28 Bengkulu Utara - Agustian, Febri; Personi, Megi; Sumantri, Ajis (Multidisciplinary Journals, 2026)
This study aims to determine the effect of Fartlek training on the maximum aerobic capacity of extracurricular futsal students at SMPN 28 North Bengkulu. This type of research is an experimental study with a sample of 20 players. The results of this study are that Fartlek training carried out by players can increase the maximum aerobic capacity of extracurricular students at SMPN 28 North Bengkulu, with t hit (6.84) > t tab (2.26). The results of this study indicate that the Fartlek training method has a significant effect on the maximum aerobic capacity of players. There is a difference in both maximum aerobic capacities before and after doing Fartlek training. The maximum aerobic capacity after being given Fartlek training treatment clearly increased, although the increase was only slight. This can be seen from the difference between the average before Fartlek training. (38.3) with the average after Fartlek training (42.2) is 3.8. Thus, there is a significant effect of the Fartlek training method on the maximum aerobic capacity of players.